Female sex and femininity independently associate with common somatic symptom trajectories. Issue 11 (10th August 2022) - Ballering, Aranka V.; Wardenaar, Klaas J.; olde Hartman, Tim C.; Rosmalen, Judith G. M.
Abstract: Background: Multiple predictors have been associated with persistent somatic symptoms. However, previous studies problematically defined the persistence of symptoms, conflated participants' sex and gender, and focused on patient populations. Therefore, we studied associations between predictors, especially sex and gender, and longitudinal patterns of somatic symptoms in the general adult population. We also assessed whether predictors for persisting symptoms differ between sexes. Method: To identify developmental trajectories of somatic symptoms, assessed by the SCL-90 SOM, we used latent class trajectory modeling in the Dutch Lifelines Cohort Study [ N = 150 494; 58.6% female; median time to follow-up: 46.0 (min–max: 22.0–123.0) months]. To identify predictors of trajectories, we applied multiple logistic regression analyses. Predictors were measured by surveys at baseline and a composite gender index was previously developed. Results: A five-class linear LCGA model fitted the data best: 93.7% of the population had a stable symptom trajectory, whereas 1.5% and 4.8% of the population had a consistently increasing or decreasing symptom trajectory, respectively. Female sex predicted severe, stable symptom severity (OR 1.74, 95% CI 1.36–2.22), but not increasing symptom severity (OR 1.15, 95% CI 0.99–1.40). Femininity was protective hereof (OR 0.60, 95% CI 0.44–0.82 and OR 0.66, 95% CI 0.51–0.85, respectively). Merely a few predictors of symptom severity, for instance hours of paid employment and physical functioning, differed in strength between sexes. Yet, effect sizes were small. Conclusion: Female sex and femininity predict symptom trajectories. No large sex differences in the strength of additional predictors were found, thus it may not be clinically useful to distinguish between predictors specific to male or female patients of persistent somatic symptoms.